Demethylzeylasteral targets lactate by inhibiting histone lactylation to suppress the tumorigenicity of liver cancer stem cells. (July 2022) - Pan, Lianhong; Feng, Fan; Wu, Jiaqin; Fan, Shibing; Han, Juanjuan; Wang, Shunxi; Yang, Li; Liu, Wanqian; Wang, Chunli; Xu, Kang
Abstract: Cancer stem cells drive tumor initiation, progression, and recurrence, which compromise the effectiveness of anti-tumor drugs. Here, we report that demethylzeylasteral (DML), a triterpene anti-tumor compound, suppressed tumorigenesis of liver cancer stem cells (LCSCs) by interfering with lactylation of a metabolic stress-related histone. Using RNA sequencing (RNA-seq) and gas chromatography-mass spectrometric (GC-MS) analysis, we showed that the glycolysis metabolic pathway contributed to the anti-tumor effects of DML, and then focused on lactate downstream regulation as the molecular target. Mechanistically, DML opposed the progress of hepatocellular carcinoma (HCC), which was efficiently facilitated by the increase in H3 histone lactylation. Two histone modification sites: H3K9la and H3K56la, which were found to promote tumorigenesis, were inhibited by DML. In addition, we used a nude mouse tumor xenograft model to confirm that the anti-liver cancer effects of DML are mediated by regulating H3 lactylation in vivo. Our findings demonstrate that DML suppresses the tumorigenicity induced by LCSCs by inhibiting H3 histone lactylation, thus implicating DML as a potential candidate for the supplementary treatment of hepatocellular carcinoma. Graphical Abstract: ga1 Highlights: Demethylzeylasteral suppressed tumorigenesis of liver cancer stem cells. H3 histone lactylation contributed to the progression of hepatocellular carcinoma. Demethylzeylasteral decreased the expression of lactate which further suppressed the H3 histone lactylation. Two histone modification sites H3K9la, H3K56la were identified to promote tumorigenesis.